The relationships among innovation strategy, atmosphere, culture, innovativeness and organizational performance in hotel industry of Thailand - Phankhong, Thienchai (2022)
The main objective of this study is to examine the mediating role of innovativeness in the relationship among innovation strategy, organisational atmosphere, organisational culture, and hotel performance in Thailand. The study employed a quantitative method. The population of this study consisted of three to five-star hotels in Thailand. Questionnaires were personally administrated to 381 respondents. One hundred and eighty-eight responses were returned from top-level hotel managers, yielding a response rate of 49%. This study adopted the SmartPLS v3.0 and the Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the research hypotheses. The findings found that innovation strategy did not show a direct effect on hotel performance as expected. On the contrary, organisational atmosphere, organisational culture, and innovativeness have a positive effect on hotel performance. The theoretical implication of the study shows that innovativeness has a significant mediating role on the path between organisational atmosphere and organisational culture on hotel performance. The result provides support for the Resource-Based View and Dynamic Capability Theory. The study suggests that hotel owners/managers should support innovation strategies to improve hotel performance. Furthermore, an appropriate organisational atmosphere and organisational culture to enhance organisational innovativeness and hotel performance should be developed. Finally, Thailand policymakers should design policies to support the development of hotels by offering training programs to enhance organisational innovativeness capability.